2004
DOI: 10.17816/vto200411145-46
|View full text |Cite
|
Sign up to set email alerts
|

Hamstring Syndrome (Clinical Manifestation, Diagnosis, Treatment)

Abstract: For the first time in native practice the approaches to diagnosis of insufficiently studied pathology - hamstring syndrome were detected. Method of operative treatment was elaborated and successfully used at clinic. In 12 patients the 2 years follow up results of operative treatment were good.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
0
0
Order By: Relevance
“…11th International Ceramics Congress 1.a. It has been reported that this salt has some water molecules bonded to the cation and others bonded to the anion, so that some intermediate salts are obtained from its thermal decomposition [31,32]. The first peak at ≈ 120ºC, with a weight loss ≈ 33%, corresponding to 12 moles of H 2 O, suggests that not all the molecules of water associated to the salt are lost and the compound Al 2 (SO 4 ) 3 •6H 2 O has probably been formed [32].…”
mentioning
confidence: 99%
“…11th International Ceramics Congress 1.a. It has been reported that this salt has some water molecules bonded to the cation and others bonded to the anion, so that some intermediate salts are obtained from its thermal decomposition [31,32]. The first peak at ≈ 120ºC, with a weight loss ≈ 33%, corresponding to 12 moles of H 2 O, suggests that not all the molecules of water associated to the salt are lost and the compound Al 2 (SO 4 ) 3 •6H 2 O has probably been formed [32].…”
mentioning
confidence: 99%